2018
DOI: 10.1139/cjfr-2016-0481
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptations and phenotypic plasticity may render gypsy moth and nun moth future pests in northern European boreal forests

Abstract: Phenotypic plasticity and local adaptations are important factors in predicting range expansions and shifts of pest insects in a changing climate. We reared two lepidopteran forest pests, Lymantria monacha (Linnaeus) and Lymantria dispar (Linnaeus), at three climatically different field sites from central Germany to northern Finland to investigate differences among populations in plasticity in the timing of pupation and adult emergence (measured as cumulative temperature sums, degree-days >5 °C), pupal mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…Previous studies on life-history traits have found mixed results regarding consistent plastic responses of traits in invasive insects as fecundity, offspring survival and developmental time to temperature (e.g. Kingsolver et al 2007;Terblanche et al 2010;Ferrer et al 2014;Fält-Nardmann et al 2018). Invasive H. axyridis performed better over a broader range of conditions than C. lunata for the majority of life-history traits (with the exception of hatching success and developmental time) but we found no notable differences in plasticity of these traits between species.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies on life-history traits have found mixed results regarding consistent plastic responses of traits in invasive insects as fecundity, offspring survival and developmental time to temperature (e.g. Kingsolver et al 2007;Terblanche et al 2010;Ferrer et al 2014;Fält-Nardmann et al 2018). Invasive H. axyridis performed better over a broader range of conditions than C. lunata for the majority of life-history traits (with the exception of hatching success and developmental time) but we found no notable differences in plasticity of these traits between species.…”
Section: Discussioncontrasting
confidence: 58%
“…It is possible that adaptive phenotypic plasticity, i.e. the ability of the same genotype to produce different phenotypes under different conditions, plays a role in the cold hardiness of L. monacha; however, this cannot be assessed based on our experiment, as the Finnish and German L. monacha were reared in the same conditions (but see Fält-Nardmann et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Controlled laboratory experiments, moreover, have shown that gypsy moths reared at higher temperatures experience reduced pupal mass and increased development times (Logan et al, ; Thompson et al, ), both of which are likely to lower fitness (Calvo & Molina, ; Honěk, ; Myers, Malakar, & Cory, ). Low temperatures have also been shown to have negative consequences for development in European gypsy moth, with some populations displaying patterns of adaptive variation (Fält‐Nardmann, Klemola, et al, ; Fält‐Nardmann, Ruohomäki, Tikkanen, & Neuvonen, ). In general, these traits are also heritable, with those related to development time and pupal mass having heritabilities varying from 0.181 to 0.703 (Janković‐Tomanić & Lazarević, ; Lazarević, Nenadović, Janković‐Tomanić, & Milanović, ; Lazarević, Perić‐Mataruga, Ivanović, & Anđelković, ; Lazarević, Perić‐Mataruga, Stojković, & Tucić, ; Lazarević, Peric‐Mataruga, & Tucić, ; Páez, Fleming‐Davies, & Dwyer, ).…”
Section: Introductionmentioning
confidence: 99%